Pengaruh Kompetensi dan Independensi Terhadap Efektivitas Audit Internal Serta Dampaknya pada Tata Kelola Pemerintah yang Baik: Studi Pada Inspektorat Kota Gorontalo - Sriwahyuni Yusup; Usman; Victorson Taruh (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of competency and independence on the effectiveness of internal audit and its impact on good government governance (Study at the Gorontalo City Inspectorate). The type of method used in this research is a quantitative method with data collection techniques using primary data. The number of samples in this research is 56 samples in 2020-2022. The tool used in this research uses Path Analysis.The results of this research show that competence and independence have a positive and significant effect on the effectiveness of internal audit through good government governance.